Analisis Efisiensi Bank Pembiayaan Rakyat Syariah (BPRS) Dan Bank Pembiayaan Rakyat (BPR) Konvensional Di Sukoharjo Dengan Menggunakan Metode Data Envelopment Analysis (DEA) Periode 2013-2015 - Quruta'ayun, Mei Lina; , Ir. Maulidiyah Indira Hasmarini, MS; , Dr. Imron Rosyadi, M.Ag (2017)
This study aims to determine the level of efficiency of Shariah and conventional BPR BPR during the period 2013-2015 and whether there is a significant difference between the level of efficiency of conventional BPR BPR sharia in Sukoharjo by using Data Envelopment Analysis (DEA) Input-oriented approach in the period 2013-2015. By using secondary data obtained from the quarterly financial statements in Sukoharjo which has been published on the official website of the Financial Services Authority (FSA) is www.ojk.go.id. BPR is said to have an efficient performance if it has a score of 1 or 100% efficiency and is said to be increasingly inefficient if close to 0. The sample used in this study amounted to 5 BPR, which consists of 1 BPR sharia and 4 BPR conventional during the period 2013-2015. Inputs used in this study is the savings, deposits, capital while the output used is financing, and placements with other banks. Based on calculations using the DEA DEAP software version 2.1, in the fourth quarter of 2013 there were 4 BPR efficient, in the first quarter 2014, there are 4 BPR efficient, in the second quarter 2014, there are 4 BPR efficient, in the third quarter 2014, there are 4 BPR efficient, in the fourth quarter 2014, there are 4 BPR efficient, in the first quarter 2015, there are 4 BPR efficient, in the second quarter 2015, there are 3 BPR efficient, in the third quarter 2015, there are 4 BPR efficient, in the fourth quarter 2015 there were 5 BPR efficient.